Just us women - Caines, Jeannette Franklin; Cummings, Pat (New York Scholastic, 1982)
A young girl and her favorite aunt share the excitement of planning a very special car trip for just the two of them
Hurg
5 18
Keywords: Aunts -- Fiction; Travel -- Fiction